Markalaşmanın Türkiye ihracatı üzerine etkileri - Çelik, Pınar (My University, 2005)
INFLUENCES OF BRAND MAKING ON THE EXPORT CAPACITY OF TURKEY It is absolute necessity to be a brand or to create a brand for gaining reputation and competability in the presnt economical requirements of the world. Low prices (affordability) or high quality do not suffice alone for survival under the heavy and complicated circumstances of global competition. A well-known and well-accepted brand name is the main feature of modern competition in the world market, now a days. Developed companies of the modern world have discovered the importance of the brand long before and have established assets accordingly. However, in our country, brand making strategies have been discovered in the last decade only. It is in this decade that the conferences and seminars are being held, brand consultancy companies are being founded and the interested companies are being extended the government support. Turquality concept have been established for setting up the quality and reliability standards, with the intention of determinig the distinguished Turkish products which meet such standards and therefore deserve to be supported with brand making and publicising. The economical crisis periods experienced in the last few years have highlighted the importance of exporing capability for which brand making is an absolute necessity. A company which plans to create a brand with such an intention shall have to keep in mind the fact that brand making is a long-term strategy and requires offical registiration and a brand image. Result of such a strategy can not be seen instantly, due to the fact that is something new for our country. However, Aydınlı Group, having its place amoung the leading 500 companies of Turkey and being internationally well-known, has initally gained the know-how by investigating the internationally known brands after which has developed its own brand, assigned considerably high budgets to brand image making and has now reached at the stage of observing the advantages of the brand in the form of enhanced export capability.

MARKALAŞMANIN TÜRKİYE İHRACATI ÜZERİNE ETKİLERİ Günümüz dünya ekonomik koşullarında söz sahibi olabilmek ve güçlü bir şekilde rekabet avantajı kazanabilmek için marka olmak ve marka yaratmak şarttır. Her geçen gün ağırlaşıp zorlaşan küresel rekabet koşullarında artık en önemli kriter ucuz fiyatlar ya da kalite değildir. Bu unsurlar bir malın olmazsa olmazdır. Artık dünya da modern rekabetin değişmez unsuru markadır. Batı'daki şirketler uzun yıllar önce marka konusunu keşfettikleri için marka konusunda ciddi yatırımlar yapmışlardır. Buna karşın bizim ülkemizde markalaşma ve marka yaratma stratejileri son yıllarda keşfedilmiş ve markalaşma kavramını yaymak için konferanslar düzenlenmiş, marka danışmanlık firmaları kurulmuş, devlet de yardımlarıyla firmaları desteklemiştir. Özellikle son günlerde Turquality ile belirli kalite ve güvenilirlik standartları oluşturulup, sonrasında ise bu standartları karşılayan Türk ürünlerinin bu kalite damgası altında tanıtılması ve markalaşması amaçlanmıştır. Son yıllarda yaşanan krizler sonucunda bir ülkede ihracatının çok önemli olduğu daha da iyi anlaşılmıştır ve ihracatı arttırmak için de markalaşmanın olmazsa olmaz koşul olduğu görülmüştür. Bunun için bir firma marka yaratırken öncelikle markanın uzun vade de bir yatırım olduğunu unutmayıp, onu tescil ettirmeli ve marka imajı yaratmalıdır. Ülkemizde bu kavram yeni olduğu için ihracat rakamları üzerindeki etkisini hemen göremeyiz. Ancak Aydınlı group gibi her yıl Türkiye'de ilk 500'e giren uluslar arası bir firma, markalaşmayı öncelikle uluslar arası markalardan öğrenmiş, daha sonrasında ise kendi markalarını yaratmış ve markalaşma adına ciddi bütçeler ayırarak markalaşmanın avantajlarını ihracat rakamlarında görmüşlerdir.
Keywords: İhracat_Türkiye; Markalaşma; Uluslararası Ticaret